2021
DOI: 10.3892/ol.2021.12975
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of differentially expressed genes reveals the promotive effects of UBE2T on colorectal cancer cell proliferation

Abstract: Colorectal cancer (CRC) is one of the most common malignancies worldwide. Via analysis using The Cancer Genome Atlas database, the present study identified 1,835 genes that were differentially expressed in CRC, including 811 upregulated and 1,024 downregulated genes. Enrichment analyses using the Database for Annotation, Visualization and Integrated Discovery tool revealed that these differentially expressed genes were associated with the regulation of CRC progression by modulating multiple pathways, such as '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The dysregulation of UBE2T is closely related to the occurrence and development of various tumors [ 39 , 40 ]. Although a previous study has shown that UBE2T was elevated markedly in non-small cell lung cancer tissues and ranked first according to the hazard ratio in the survival analysis [ 18 ], the functional role and molecular mechanism of UBE2T in LUAD proliferation and metastasis remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of UBE2T is closely related to the occurrence and development of various tumors [ 39 , 40 ]. Although a previous study has shown that UBE2T was elevated markedly in non-small cell lung cancer tissues and ranked first according to the hazard ratio in the survival analysis [ 18 ], the functional role and molecular mechanism of UBE2T in LUAD proliferation and metastasis remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, UBE2S may be an emerging target for CRC treatment ( 105 ). Luo and Zhou ( 106 ) and Wu et al ( 107 ) demonstrated that UBE2T expression was elevated in CRC tissues and samples and that elevated UBE2T was associated with reduced OS time in clinical patients. It promotes the proliferation, migration and invasion of CRC cells and inhibits apoptosis.…”
Section: Class III E2s In Digestive System Cancersmentioning
confidence: 99%